Ekosistem mangrove sebagai habitat kepiting bakau (Scylla Serrata) di Kampung Nipah Desa Sei Nagalawan Kecamatan Perbaungan Serdang Bedagai Provinsi Sumatera Utara - Sari Marina Saragi; Desrita Desrita (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2018)
Highly Utilization of Mangrove field as cultivation field of fish and recreation and tour site by people have big posses to the abundance of Mangrove crab (Scylla serrata) because of mangrove play role as habitats of mangrove crabs. The research was conducted for two months from December 2016 to January 2017. This study aims to see the structure of mangrove vegetation, the abundance of Mangrove Crab and the influence of mangrove vegetation structure on the abundance of Mangrove Crab in Kampung Nipah. The results of this research are Vegetation structure of Mangrove in the station I and II show high density, whereas density in station III wide apart. The abundance of mangrove crab in the station I and II showed the higher result from station III. The Influence of Vegetation Structure of Mangrove and Abundance of Mangrove Crab can be related by using regression analysis Y = 0.0241x + 113.6. The correlation coefficient (r) that value obtained as 0.79 have a meaning the connection between mangrove density and abundance of mangrove crab are rated in the strong category that has a value 79%. The density of Mangrove to 1000 units will rise up the abundance of mangrove crab to 43.5 an individual.Tingginya pemanfaatan mangrove sebagai lahan budidaya ikan dan sebagai wisata rekreasi oleh masyarakat sangat mempengaruhi kelimpahan Kepiting Bakau (Scylla serrata) karena hutan mangrove merupakan habitat bagi Kepiting Bakau. Penelitian ini dilaksanakan selama dua bulan yaitu bulan Desember 2016 sampai Januari 2017. Penelitian ini bertujuan untuk melihat struktur vegetasi mangrove, kelimpahan Kepiting Bakau dan pengaruh struktur vegetasi mangrove terhadap kelimpahan Kepiting Bakau di Kampung Nipah. Hasil dari penelitian struktur vegetasi mangrove di stasiun I dan II memiliki kerapatan sangat padat, sedangkaan kerapatan di stasiun III jarang. Kelimpahan Kepiting Bakau di Stasiun I dan II lebih tinggi dari kelimpahan di stasiun III. Pengaruh kerapatan mangrove dan kelimpahan Kepiting Bakau diperoleh persamaan regresi yaitu Y = 43,521 + 0,2061x. Koefisien korelasi (r) yang diperoleh 0,79 yang artinya hubungan kerapatan mangrove dan kelimpahan Kepiting Bakau tergolong kuat yaitu sebesar 79%. Kerapatan mangrove sebanyak 1000 satuan akan meningkatkan kelimpahan Kepiting Bakau sebesar 43,5 individu.